Effect of B-site substitution on structural, magnetic and optical properties of Ho2Ti2O7 pyrochlore oxide - Yadav P.K.; Singh P.; Shukla M.; Banik S.; Upadhyay C. (My University, 2025)
Ho2Ti2O7 is a prominent quantum material, known for its exotic spin ice state, where structural and electronic properties are coupled. We report the systematic examination of the effects of Fe substitution at the non-magnetic Ti site (x = 0, 0.05, 0.075, 0.1, 0.125 and 0.15) in Ho2Ti2O7 on the structural, optical and magnetic properties. It is found that the optical properties of polycrystalline Ho2Ti2-xFexO7-δ (x = 0, 0.05, 0.075, 0.1, 0.125 and 0.15) can be tuned through partial substitution of the trivalent Fe3+ ion for the tetravalent Ti4+ ion. This Fe substitution not only creates charge-compensating oxygen vacancies but also modifies the optical band gap. A systematic structural, X-ray photoelectron spectroscopy, magnetic and optical analysis reveals that above a critical content of x = 0.1, a possible reduction in the oxygen coordination number (octahedral to tetrahedral) occurs, which appears in the form of high spin to low spin crossover for a fraction of the substituted Fe3+ ions. These results provide a new route to tune the optical band gap and absorption coefficient of Ho2Ti2O7 for magneto-optical applications. © 2019